A phase 2 study of rituximab, cyclophosphamide, bortezomib and dexamethasone (R-CyBorD) in relapsed low grade and mantle cell lymphoma. Issue 9 (2nd September 2018) - Sonbol, Mohamad Bassam; Hilal, Talal; Dueck, Amylou C.; Rosenthal, Allison C.; Conley, Christopher R.; Kosiorek, Heidi E.; Ginos, Brenda F.; Gano, Katherine M.; Nichols, Craig S.; Leis, Jose F.; Johnston, Patrick B.; Habermann, Thomas M.; et al.
Abstract: In this phase 2 trial, we sought to evaluate the efficacy and safety of rituximab, cyclophosphamide, bortezomib, and dexamethasone (R-CyBorD) in patients with low-grade NHL. The regimen included rituximab on day 1 with weekly cyclophosphamide, dexamethasone, and bortezomib 1.3 mg/m 2 IV in a 28-day cycle. Twenty one patients were enrolled on the study. Median age was 69 years (range 51–80) and 17 (81%) patients had two or more prior treatments. Histologies included FL ( n = 8), MCL ( n = 8), and LPL/WM ( n = 5). Hematologic toxicity and peripheral sensory neuropathy were the most common adverse events. With a median follow-up of 38.1 months, ORR was 13/21 (62%), with 4 (19%) CR. The ORR was 7/8 (88%) in FL and was 4/5 (80%) in LPL/WM. Median PFS and OS were 11.6 months and 54.8 months, respectively. R-CyBorD is an effective regimen in relapsed FL and LPL/WM patients with an acceptable safety profile.